2012
DOI: 10.4081/gh.2012.104
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal relationship between normalized difference vegetation index and abundance of the Phlebotomus kala-azar vector in an endemic focus in Bihar, India

Abstract: Abstract.Remote sensing was applied for the collection of spatio-temporal data to increase our understanding of the potential distribution of the kala-azar vector Phlebotomus argentipes in endemic areas of the Vaishali district of Bihar, India. We produced monthly distribution maps of the normalized difference vegetation index (NDVI) based on data from the thematic mapper (TM) sensor onboard the Landsat-5 satellite. Minimum, maximum and mean NDVI values were computed for each month and compared with the concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Case–control studies in India confirmed that rural households in close proximity to waterbodies were at greater risk of VL than those apart [40, 94]. Bhunia et al [39, 90] examined the effect of waterbodies/NDWI derived from satellite data on VL cases and reported a strong association, which agrees with our finding. Their study further revealed that VL cases decreased with increased distance from waterbodies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Case–control studies in India confirmed that rural households in close proximity to waterbodies were at greater risk of VL than those apart [40, 94]. Bhunia et al [39, 90] examined the effect of waterbodies/NDWI derived from satellite data on VL cases and reported a strong association, which agrees with our finding. Their study further revealed that VL cases decreased with increased distance from waterbodies.…”
Section: Discussionsupporting
confidence: 90%
“…It is, thus, reasonable to assume that moist conditions resulting from heavy rainfall lead to the occurrence of the disease and possibly support sand fly emergence and abundance, especially in the study area, because high humidity is a prerequisite for their survival [38, 89]. Humidity determines the extrinsic incubation and vector life cycle, and Bhunia et al [90], for example, observed that the abundance of P. argentipes in Bihar was associated with high humidity and heavy rainfall. Our results differ slightly from those of similar studies in Iran [91], India [39, 89], and Sudan [38] in which annual rainfall, rather than precipitation during a certain period, was reported as an influential factor affecting the distribution of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate moisture is necessary for the developmental stages of the vector, whereas sugar resources are essential for adult sandf lies. Previous studies have shown overlapping vegetation and VL incidence and vector abundance [31]. A close relationship was found between vegetation coverage intensity and seasonal vector abundance.…”
Section: Discussionsupporting
confidence: 55%
“…The importance of considering NDVI was demonstrated with respect to the distribution of the reservoir Psammomys obesus (sand rat) and the distribution of its primary food, chenopods (Toumi et al., 2012). NDVI has been implicated as a key explanatory variable in the distribution of leishmaniasis cases in several studies (Cross et al, 1996; Thomson et al, 1999; Elnaiem et al, 2003; Gebre-Michael et al, 2004; Elnaiem, 2011; Hartemink et al, 2011; Bhunia et al, 2012; Toumi et al, 2012; de Oliveira et al, 2012). …”
Section: Methodsmentioning
confidence: 99%